Internationalization field lab of ps: an in-depth analysis of Germany - Kantenwein, Vivienne Marielle (2022)
Internationalization is a strategic challenge for small companies. This paper aims to provide an analytic procedure for the Portuguese luxury real estate agency of PS by defining the target market for expansion, an appropriate market entry mode, and an applicable marketing plan along a financial forecast. Literature was reviewed to identify the criteria real estate investors use to choose international markets. An in-depth analysis of Germany revealed that while it offers a favorable environment for operating as a real estate broker with a focus on international clients, the tax system, local competition, and bureaucracy reduce the country’s attractiveness.